KARAKTERISASI FRAKSI AKTIF ANTIBAKTERI EKSTRAK DARI DAUN PEPE (Gymnema reticulatum Br) - I M. Dira Swantara; I. B. Darmayasa; Sri lestari (Jurnal Kimia (Journal of Chemistry), 2010)
Isolation and caracterisation of antibacterial compounds in the leaves pepe have been carried out. Extractionwas carried out by macerating using methanol and 70%. Separation of extracts which have activity to Eschericia coliand Stathylococcus aereus was conducted using the solvent partition by petroleum ether, chloroform, and ethylacetate. The most active extract, the ethyl acetate extract was separated by column chromatography using a mixtureeluent of chloroform, and ethyl acetate with a ratio of 1:1. The eluents were tested for their bioactivity asantibacterial agent and the results established that fraction 1 was the most active fraction. This next wing fraction 1was then identified using GC-MS.The gas chromatogram showed 3 peaks at 18.658 minutes (33.69%), 19.617 minutes (34.01%), and 25.492minutes (32.69%). It was suggested that the fraction contains three compounds. The first peak has a molecularion atm/z 296 with a base peak of 68, matches with the spectra of 3,7,11,15-tetramethyl 2-hexadesene-1-ol. The secondpeak, m/z 270 and 74, matches with the spectra of metyl hexadecanoate ester. The last peak has amoleculer ion at390 and base peak at 149, suggesting it is dioctyl-1,2-benzenedicarboxylilate.